Nilai-Nilai Pendidikan Akhlak Dalam Kitab Risalatul Muawanah Karya Sayyid Syarif Abdullah Bin Alwi Bin Muhammad Al-Haddad (Bab Menjaga Adab-adab Tingkah Laku) - Zaidatun Ni’mah Julifiyana; Ngarifin Shidiq; Nur Farida (CV. KAMPUS AKADEMIK PUBLISING, 2025)
. In the midst of global challenges such as moral degradation, individualism, and the rise of hate speech, strengthening ethical and moral values has become an urgent need in the field of education. Islam, as a comprehensive religion, emphasizes the importance of morality through teachings derived from the Qur’an, Hadith, and classical scholarly works. This article aims to examine the moral educational values contained in the chapter